Instructional Design of Artificial Intelligence Course through Curriculum Innovation Based on Outcome Based Education (OBE) - Kisno K.; Suryadi; Nia Fatmawati (Jurnal Edutech Undiksha, 2025)
The development of an Outcome-Based Education (OBE) curriculum for Artificial Intelligence (AI) courses is an urgent need to align with technological advancements and evolving learning demands. This study aims to design an instructional framework for an Artificial Intelligence course through OBE-based curriculum innovation. The need for an OBE curriculum emphasizes measurable learning outcomes that are relevant to workforce demands, requiring systematic instructional planning. The research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through literature review, curriculum document analysis, and expert validation. The results indicate that the developed instructional design successfully integrates course learning outcomes with graduate profiles and produces learning tools such as a semester learning plan, teaching modules, and OBE-based assessment instruments. The discussion highlights the importance of aligning instructional design with the needs of the digital workforce. Findings suggest that the OBE-based instructional design for the AI course is highly feasible for implementation and enhances the relevance of graduate competencies to labor market demands. This study provides positive implications for institutions, study programs, lecturers, and students by offering a clear, systematic, and measurable guideline for designing AI learning that is relevant to both educational needs and the world of work.